Derivation of Naïve Human Embryonic Stem Cells Using a CHK1 Inhibitor - Carol B. Ware; Erica C. Jonlin; Donovan J. Anderson; Christopher Cavanaugh; Jennifer Hesson; Sonia Sidhu; Savannah Cook; Guillermo Villagomez-Olea; Marshall S. Horwitz; Yuliang Wang; Julie Mathieu (Stem Cell Reviews and Reports, 2023)
Embryonic development is a continuum in vivo . Transcriptional analysis can separate established human embryonic stem cells (hESC) into at least four distinct developmental pluripotent stages, two naïve and two primed, early and late relative to the intact epiblast. In this study we primarily show that exposure of frozen human blastocysts to an inhibitor of checkpoint kinase 1 (CHK1) upon thaw greatly enhances establishment of karyotypically normal late naïve hESC cultures. These late naïve cells are plastic and can be toggled back to early naïve and forward to early primed pluripotent stages. The early primed cells are transcriptionally equivalent to the post inner cell mass intermediate (PICMI) stage seen one day following transfer of human blastocysts into in vitro culture and are stable at an earlier stage than conventional primed hESC. Graphical Abstract